The impact of exchange rate volatility on bilateral export with the United States in selected high performing East Asian economies - Vanhnalat, Bounlert (Animo Repository, 2006)
The impact of exchange rate volatility on trade flows are still complicated issues in obtaining the net effect. This study estimates the impact of exchange rate volatility of HPAEs countries: Japan, Singapore, South Korea, Hong Kong, and Thailand together with their dominant trading partner the United States for the period of January 1992:01 to February 2005. Both the moving average standard deviation (MASD) and GARCH approaches are used in measuring exchange rate volatility. The Johansen cointegration technique and vector error correction model are also used to obtain the long run elasticities and short-run dynamics. The findings suggest that the volatile exchange rates are indeed significant and can adversely affect HPAEs exports, except in the case of Hong Kong and South Korea. Moreover, the exchange volatility measured by MASD and GARCH provided the different effect on exports.